Weak Law Enforcement in Cases of Violence Against Women with Disabilities - Faridah, Siti (Universitas Negeri Semarang, 2019)
Women are created by God and have the same rights as men without any restrictions or other things that discredit equal equality. The echoes and shouts for gender equality are motivated by the politics of marginalization of women which reflects indirect acts of discrimination. In addition, women with disabilities have double discrimination because of their disability and because they are women. Many cases and law enforcement have not been completed against women with disabilities because of negative stereotypes in society that do not protect and support the fulfillment of their basic rights. In fact, many cases that occur do not have serious treatment and instead end up only in psychological and psychosocial assistance.